Caloric restriction induced epigenetic effects on aging - Zhai, Jingfang; Kongsberg, William H.; Pan, Yinbo; Hao, Canhua; Wang, Xiaojing; Sun, Jie (Frontiers in Cell and Developmental Biology, 2023)
Aging is the subject of many studies, facilitating the discovery of many interventions. Epigenetic influences numerous life processes by regulating gene expression and also plays a crucial role in aging regulation. Increasing data suggests that dietary changes can alter epigenetic marks associated with aging. Caloric restriction（CR）is considered an intervention to regulate aging and prolong life span. At present, CR has made some progress by regulating signaling pathways associated with aging as well as the mechanism of action of intercellular signaling molecules against aging. In this review, we will focus on the molecular mechanisms by which CR delays aging through autophagy, epigenetic modification. As well as the interaction between autophagy and epigenetics in caloric restriction, in order to provide new ideas for the study of the mechanism of aging and delaying aging.